USING ORIGAMI TO ENHANCE VISUAL AND MATHEMATICAL THINKING SKILLS AMONG THE AUTISTICS - Wan Norliza Wan Bakar; Fatimah Zuhaira Yusoff Fauzi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Autism is a general term for a group of complex disorders that affects brain development (Autism Society of America, (2014). â€œAutosâ€ means â€˜you in your own selfâ€™ which is described as â€˜a runaway from realityâ€™ (Leo Kanner, (1943). Autism has its own specializations which are mathematical (Baron Cohen et al 2001), and visual thinkers (Karren Piece, 2010). They can follow steps and create designs in more creative ways than others. This paper will deliberate on how origami technique helps escalate the development of mathematical and visual thinking skills of the autistic people. Three autistics namely Cheâ€™ Suria Aishah Farhana binti Cheâ€™ Mat, an Asperger Syndrome Autistic, Muhamad Aliff Najmi bin Cheâ€™ Kamarudin, a Classic Autistic and Mohamad Aizuddin, a Pervasive Developmental Disorder Autistic were selected. They are from a special inclusive class of SMK Kadok, Kelantan in the eastern part of West Malaysia. Based on the objectives of this research paper a qualitative study was implemented. The triangulation method comprising of observation, interview and analysis were applied. The results revealed that the Asperger Syndrome Autistic has a very systematic way in learning. Her ability to develop new ideas and new designs indicates that she is a mathematical and visual thinker. The Classic Autistic too has a systematic way of learning and is able to innovate new designs proves that he is a mathematical and visual thinker. On the other hand, the Pervasive Developmental Disorder autistic was not interested in origami. He just stared at the origami and showed no interest in it. Future research can be implemented on how to capture the interest of the Pervasive Developmental Disorder autistics.